Automatic Water Tank Filling Simulation Based on LabVIEW - Agung Rizky Jamas; Ryan Adam Hidayatullah; Ratnasari Ratnasari; Didik Aribowo; Ismah Nurul Sya’bani (Universitas Nusa Putra, 2023)
Automatic tank filling is the process of filling water in the tank in a more efficient way or automatically without having to be controlled manually. How to simulate it by compiling a schema using the Labview application. When it is planned, a simulation will produce a predetermined schema. With the simulation of filling the tank water using the Labview application, it becomes more effective because it becomes automatic when the water tank is empty, the machine will turn on and fill the water in the tank and vice versa when the water tank is full, the machine will turn off, and also the capacity of the water in the tank can be estimated. . So there is no need for manual control anymore. System control can be done anywhere so it will not interfere with daily activities. The system that is carried out is a system that is needed in this world so that everything goes well without interruption. The feasibility of the required system is in accordance with predetermined standards, so that there are no errors that will interfere with the system and activities that are being used. This simulation is useful to find out if there is an error in the system used in the automatic tank. Automatic tank filling is very useful for homes that have smart homes, because they can be monitored remotely via smartphones or applications used to run certain systems.